Video Content Editing as a Form of Institutional Communication Adaptation to Social Media: A Field Study of the Pusat Penerangan Mabes TNI Infonet Division - Aqsha Naurah Assifah; Abung Supama Wijaya (Communica : Journal of Communication, 2026)
This study examines the video editing process in the Infonet Division of the Indonesian Armed Forces Headquarters (Puspen TNI) as a form of institutional communication adaptation to social media. Using a qualitative case study approach through observation, interviews, and literature review, this research finds that video editing is not merely a technical activity, but a strategic communication process shaped by institutional regulations, professional norms, and shared military culture. Editors act as mediators who adapt official messages into short, vertical, and visually engaging content suitable for platforms such as Instagram Reels and TikTok, while maintaining information security and institutional professionalism. The findings reveal an ongoing tension between the cautious nature of military institutions and the dynamic character of social media, resulting in adaptive editing strategies that balance credibility and digital relevance. This study contributes to discussions on institutional adaptation in digital communication practices within public sector organizations.